‘IMMUNES’ W ARMII RZYMSKIEJ W UJĘCIU JURYSTY RZYMSKIEGO PUBLIUSA TARUTTIENUSA PATERNUSA - Faszcza, Michał Norbert; Kłodziński, Karol (Zeszyty Prawnicze, 2016)
THE ‘IMMUNES’ IN THE ROMAN ARMY ACCORDING TO THE ROMAN JURIST PUBLIUS TARUTTIENUS PATERNUS Summary The article presents the Roman jurist Publius Taruttienus Paternus, who was a praetorian prefect and military commander in the final phase of the Marcomannic Wars, and incorporates an analysis of a passage from Paternus’ Digest (D. 50,6,7). In this passage Paternus described the immunes, a category of Roman soldiers specialising in technical and medical tasks. The authors use legal, numismatic, narrative, epigraphic and papyrological sources.